2018
DOI: 10.1177/0255761418819016
|View full text |Cite
|
Sign up to set email alerts
|

A strategic approach to music listening with a mobile app for high school students

Abstract: The primary objective of this study is to investigate whether three interaction strategies through mobile apps may be associated with increases in students' music listening skills. Data was collected from 225 high school students and analysed using the ANOVA procedure in the three ways of music listening: analytic, aesthetic and sensory. Interaction with the app was least influential in the analytic listening of the participants. Interaction with peers was most influential in the aesthetic listening of the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…However, in other countries, such as Taiwan, the government has been implementing since the 1990s a series of educational policies and investments in resources that have proven their benefits (Chen, 2012). Nonetheless, we should recall that multiple applications are available through mobile phones, devices whose use is entirely widespread and habitual in Spain, that do not require the use of the tools of the classroom itself (Cho et al, 2019).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…However, in other countries, such as Taiwan, the government has been implementing since the 1990s a series of educational policies and investments in resources that have proven their benefits (Chen, 2012). Nonetheless, we should recall that multiple applications are available through mobile phones, devices whose use is entirely widespread and habitual in Spain, that do not require the use of the tools of the classroom itself (Cho et al, 2019).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…On these lines, Bauer and Dammers (2016) found similar problems in the National Association of Schools of Music (NASM; United States), where teachers regarded a lack of resources and funds as common obstacles for integrating technologies into the music teacher education curriculum. Nonetheless, we should recall that multiple applications are available through mobile phones, devices whose use is entirely widespread and habitual in Spain, that do not require the use of the tools of the classroom itself (Cho et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging technologies have already created learning opportunities that challenge the traditional pedagogical approaches in music learning through mobile services and web-conferencing software (Cho et al, 2019;Sabet, 2020). Prior studies demonstrated that recent musical instrument applications (apps) such as Echobo and Garageband could successfully engage secondary school students to participate in performing blended learning practices with their mobile devices (e.g., Lee & Freeman, 2013;Väkevä, 2010;Wise, 2016).…”
Section: Using Technology In Music Educationmentioning
confidence: 99%